The impact of student aid eligibility on higher education applications - Camille Remigereau; Clara Schäper (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
This study examines how student aid eligibility influences application decisions to higher education using administrative data from France. We study the impact of a change in income thresholds for aid eligibility. We find that aid eligibility did not have a uniform effect on students' applications but varied by gender and academic performance. Highperforming male students shifted their First-Ranked application from non-selective to selective long-term programs. Yet, female students did not show a systematic response. We suggest that female students were more certain in their application choices, while male students faced stronger financial constraints than females when attending long-term selective programs.
Keywords: I22; I23; I24; I38; J16; 330; education; inequality; financial aid; gender